Cultural hybridity and body image formation: exploring the experiences of Wushu male practitioners at the Siberian Chinese Martial Arts Center - Santanna, Ekaterina A.; Li, Benqian (Frontiers in Psychology, 2024)
This study explores the formation of a hybrid body image among white cisgender males practicing Wushu at the Siberian Chinese Martial Arts Center. Grounded in Social Identity Theory and the concept of bicultural identity, the research employs narrative interviews with 12 participants. Thematic analysis revealed three main themes: the creation of a hybrid identity blending Chinese martial arts traditions with Russian cultural backgrounds, conceptualized as judanren; the challenges associated with this identity in both Russian and Chinese contexts; and the role of Wushu uniforms in reconciling these cultural contradictions, serving as a “second skin” for practitioners. The findings contribute to a more inclusive understanding of body image and identity formation in a multicultural, non-Western context.